No evidence for a reciprocal relationship between daily self-control failures and addictive behavior in a longitudinal study - Kräplin, Anja; Joshanloo, Mohsen; Wolff, Max; Fröhner, Juliane Hilde; Baeuchl, Christian; Krönke, Klaus-Martin; Bühringer, Gerhard; Smolka, Michael N.; Goschke, Thomas (Frontiers in Psychology, 2024)
Introduction We all experience occasional self-control failures (SCFs) in our daily lives, where we enact behaviors that stand in conflict with our superordinate or long-term goals. Based on the assumption that SCFs share common underlying mechanisms with addictive disorders, we tested the hypothesis that a generally higher susceptibility to daily SCFs predicts more addictive behavior, or vice versa. Methods At baseline, 338 individuals (19–27 years, 59% female) from a community sample participated in multi-component assessments. These included among others (1) a clinical interview on addictive behaviors (quantity of use, frequency of use, DSM-5 criteria; n = 338) and (2) ecological momentary assessment of SCFs (n = 329, 97%). At the 3-year and 6 year follow-up, participation rates for both assessment parts were 71% (n = 240) and 50% (n = 170), respectively. Results Controlling for age, gender, IQ, and baseline addiction level, random-intercept cross-lagged panel models revealed that participants who reported more SCFs also showed pronounced addictive behavior at the between-person level, but we found no evidence of a predictive relationship at the within-person level over time. Discussion A higher rate of SCFs is associated with more addictive behavior, while there is no evidence of an intraindividual predictive relationship. Novel hypotheses suggested by additional exploratory results are that (1) only addiction-related SCFs in daily life are early markers of an escalation of use and thus for addictive disorders and that (2) an explicit monitoring of SCFs increases self-reflection and thereby promotes the mobilization of cognitive control in response to goal-desire conflicts.